Generativity and Adult Development: How and Why We Care for the Next Generation. 1998
DOI: 10.1037/10288-001
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of generativity.

Abstract: It requires only a passing familiarity with the popular writings of ErikErikson to have an inkling of what the concept of generativity is all about.It is about the next generation, about bearing, raising, caring for children -one's own and others. It is about assuming the role of responsible parent, mentor, shepherd, guardian, guide, and so on, vis-8-vis those whose development and well-being benefit from the care that role provides. It is even about assuming such a role vis-S-vis society writ large, about bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(131 citation statements)
references
References 22 publications
(30 reference statements)
4
120
0
7
Order By: Relevance
“…More recently, in a psychosocial approach, McAdams and de St. Aubin (1992) proposed a holistic representation of generativity that links the person and the social world. McAdams, Hart, and Maruna (1998) suggest that this theory of generativity includes seven features: (1) There is a personal inner desire for symbolic immortality (the desire to defy death by constructing legacies that live on) and the need to be needed by others (an expression of communion relating to others in loving, caring, and so on). (2) There is a cultural demand which encompasses a wide spectrum of factors external to the individual (developmental expectations and societal opportunities) that could offer an adult the ability to shape her/his generative inclinations.…”
Section: Generativitymentioning
confidence: 99%
“…More recently, in a psychosocial approach, McAdams and de St. Aubin (1992) proposed a holistic representation of generativity that links the person and the social world. McAdams, Hart, and Maruna (1998) suggest that this theory of generativity includes seven features: (1) There is a personal inner desire for symbolic immortality (the desire to defy death by constructing legacies that live on) and the need to be needed by others (an expression of communion relating to others in loving, caring, and so on). (2) There is a cultural demand which encompasses a wide spectrum of factors external to the individual (developmental expectations and societal opportunities) that could offer an adult the ability to shape her/his generative inclinations.…”
Section: Generativitymentioning
confidence: 99%
“…Tras unas décadas de relativo olvido, la generatividad es reintroducida en los estudios sobre el desarrollo en la adultez por Dan McAdams, quien diferencia entre el interés generativo, definido como una actitud favorable hacia cuestiones generativas, y la acción generativa, o puesta en marcha y concreción en comportamientos de esa actitud favorable (McAdams y Logan, 2004;McAdams, Hart, y Maruna, 1998). Este mismo autor desarrolló instrumentos para eva-anales de psicología, 2013, vol.…”
Section: La Generatividad En La Vejezunclassified
“…Los autores atribuyen estas diferencias entre interés y actividad generativa a las diferentes oportunidades que las personas pueden tener para llevar a la práctica su interés generativo, en función de diversas circunstancias vitales o variables como el género, el nivel educativo o el estado civil (McAdams et al, 1998). Además, quizá estar implicado en acciones generativas implica mayores dificultades y sinsabores que simplemente expresar interés y preocupación por los demás (Warburton, McLaughin, y Pinsker, 2006).…”
Section: Generatividad Y Bienestar En La Vejezunclassified
“…While Chickering and Reisser (1993) advanced psychosocial research beyond stage based models, they still argued that identity formation is a primary focus of psychosocial development during college years. McAdams, Hart, and Maruna (1998), however, suggested that identity development need not be reserved for a psychosocial stage during late adolescence or early adulthood, but rather that identity development is constructed and reconstructed throughout a person's adult life through narration. Furthermore, the "generativity script" (McAdams, Hart, & Maruna, 1998, p. 12) is one piece of that life narration.…”
Section: Generativity In the College Student Contextmentioning
confidence: 99%